Forestry and Wildlife Conservation in the Tropics - Choudhury, Saroj Raj (Indian Forester, 1975)
Food and cover are the two basic qualifiers of niches in the forest. In the tropics, the immense structural diversities of forests create intricate niche-mosaics and hence, provide for numerous animal species. Mid and late successional stages in a sere hold largest number of animal species in dynamic state. Forestry under natural regeneration systems in which succession is arrested, provides more favourable site to wildlife. Harassment by persistent shootings disturbs wild animals, not forestry operations. Forester should appreciate this in his integrated view on forestry and wildlife conservation in the tropics. Silviculture should weigh the obligatory needs of ecologically and economically important wildlife species - strategic location of the ’defective’ or ’unproductive’ areas may have high environmental significance for animals. Consumable plant matter, when routed through the guts of herbivores starts off productive channels of consumable animal matter. Protein hungry tropical regions could be sizeably satisfied through considerably higher production of animal protein from mixed populations of wild herbivores in the forests worked under natural systems. Exotics replacing natural forests may be environmentally hazardous both for wildlife and the local human beings. Far-sighted coordination of forestry and wildlife conservation is hence necessary. Action, as proposed in UNESCO’s 44th session (1) is required at four levels : scientific; educational; institutional; legislative. Emphasis is stressed on simple broad-based methodologies; suitable education of the forester at different levels in wildlife conservation; stimulation of mass environmental consciousness, particularly of the local people, relating to forests and wildlife; need for adequate legislation. Differential weightage on plants and animals necessary in different types of forests have to be scientifically determined. These, to start with, could, however, be broadly guessed for principally wet zones, predominantly dry zones and regions of mixed physiognomy under edaphic influence. Main basis of coordination would be the continuing pool of spatiotemporal data on structure and function collected through forestry personnel, sequential interpretations and diagnosis followed by in-depth studies as necessary. Comparative status of different wildlife species in multiple use concept has to be evaluated. General methods of coordination are of four categories; protective for obligatory habitat qualifiers; preventives for over exploitation, diseases and to minimize silvicultural interference of functionally important pockets for animals; constructive in manipulating poor timber pockets to improve ’edge’ effect, using controlled fire as a tool, ,creating shelters while piling lops and tops, winding the roads to improve ambush cover, etc.; ameliorative, in improving limiting factors like summer scarcity of water, control of summer fires, provision of salt-licks and particular types of covers etc. Specific measures for broadly grouped silvicultural systems have been discussed. The utility of coordination should be realised in balanced and better organisation of the consumptive and non-consumptive use of wildlife by widening the scope of forestry practices, and the resultant influence of wildlife conservation on forestry to ensure environmental stability for rare and threatened species. A forest kept out of use is often left out of sight. Poacher gets better opportunities and protection becomes commulative fiscal burden. Hence, the paper ends with emphasis on the ruling objective - the multiplewise use of forests and wildlife, appropriate sharing of the benefits by the local people and stimulation of increasingly conscious desire to perpetuate the sources of benefits from plants, animals and their associates in a more wholesome environment.